Pengembangan Media Scrapbook Quis IPA Kelas IV Materi Metamorfosis Sekolah Dasar - Dewi Wulan Arum; Erwin Putera Permana; Farida Nurlaila Zunaidah (Journal on Education, 2023)
The objectives achieved in this study were to find 1) the validity of Scrapbook Quiz media on Metamorphosis material in class IV SD 2) the practicality of Scrapbook Quiz media on Metamorphosis material in class IV SD 3) the effectiveness of Scrapbook Quiz media on Metamorphosis material in IVSD class. This research is the development of the Research and Development (R&D) ADDIE development model, there are 5 namely analysis, design, development, implementation, and evaluation. The development of the Scrapbok Quiz media can be held by hand in the shape of a book containing information or explanations of the material and presented with pictures accompanied by decorations and supporting images. The Quiz Scrapbook media was validated by media experts and material experts, the results met valid criteria that could be used, media validation obtained 84% while material validation obtained 82%. So, the average percentage of media and material validation scores obtained is 83% included in the very valid category. The practicality data obtained from the class teacher obtained 86% which was stated to be very practical, then from the practicality data of students (6 students obtained a percentage of 88%) and which (17 students obtained a percentage of 90%) which means very practical. Data on the effectiveness of the Scrapbook Quiz media can be seen from the results of the completeness of class IV students in the form of test scores tested on students based on the KKM (Minimum Completeness Criteria) of 75.